Sesamolin Protects Mice From Ovariectomized Bone Loss by Inhibiting Osteoclastogenesis and RANKL-Mediated NF-κB and MAPK Signaling Pathways - Yang, Xue; Liang, Jiamin; Wang, Ziyi; Su, Yuangang; Zhan, Yunfei; Wu, Zuoxing; Li, Jing; Li, Xuedong; Chen, Runfeng; Zhao, Jinmin; Xu, Jiake; Liu, Qian; et al. (Frontiers in Pharmacology, 2021)
Postmenopausal osteoporosis (PMOP), which increases the risk of fracture, is the most common bone disease in women. PMOP not only increases the risk of death but also imposes a financial burden on countless families. At present, most of the drugs used to treat osteoporosis have significant side effects, so it is important to find effective anti-osteoporosis medications without major side effects. Sesamolin (Ses) is a kind of natural lignan extracted from sesame oil. Many researches have shown that Ses has anti-inflammatory, antioxidative, and anticancer effects, however it is still unknown whether it has any effect on osteoporosis. In this research, we explored the therapeutic effect of Ses in the process of osteoclast formation and bone resorption and found that Ses effectively inhibited osteoclast formation in vitro through TRAcP staining and hydroxyapatite resorption assays. Through Western blot analysis of the NF-κB pathway, MAPK pathway, c-Fos and NFATc1, it was found that Ses not only effectively inhibited the activation of NF-κB and MAPK signaling pathways induced by RANKL but also significantly reduced the protein expression of c-Fos and NFATc1. Several genes specifically expressed in osteoclasts were determined by qPCR, and Ses was also found to play a significant inhibitory role on the expression of these genes. Besides, an osteoporosis model induced in ovariectomized (OVX) mice was employed to verify that Ses could effectively reduce bone loss caused by estrogen deficiency in vivo. In conclusion, Ses showed promise as a new treatment for postmenopausal osteoporosis.